THE ROLE OF TIBETAN BROCADES IN VARANASI'S HANDLOOM INDUSTRY: PAST, PRESENT, AND FUTURE PROSPECTS - Tiwari, Ayush; Chaudhary, Dr. Kavita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The use of hand-woven textiles in India predates recorded history by an enormous margin. People from rural and semi-urban areas make up a large portion of this industry's workforce. Many of these craftspeople come from low-income backgrounds and are women. Some of the traits shared by this industry include the following: the availability of cheap and plentiful labour; the utilisation of local resources; the utilisation of distinctive artistry in product production; and the increasing admiration of the industry by international customers. Keep in mind that this industry contributes only a tiny fraction of India's total exports to global markets, despite its unique characteristics. Therefore, it is critical to promote and direct the industry's goods so that its untapped potential may be realized. This study aims to shed light on the cultural relevance of the handloom by offering an overview of its history, its role before and after independence, its rebirth, the technique, and the varieties of handloom that are popular in India.